Avant - Alvarez Neme, Juan, 1972- (Tarkiofilm Ltda, 2014)
A forgotten national ballet company that inhabits a theater still under construction is revolutionized with the arrival of Julio Bocca, one of the best ballet dancers of all times. After her professional retirement and looking to find a new place in the world of dance, Bocca takes on the challenge of running this company and projecting it to a level of international competition. In this company you must put your name at stake to face the dilemmas between art and management in a highly bureaucratic state structure. A group of young dancers from diverse backgrounds leave everything behind and do not hesitate to audition to be part of the new group, having to integrate with the old stable body in a field of high competition. Three brothers, a young ballet promise and a rising dancer among others, star together with Bocca this process where the details are at the same level as the big decisions. "Avant" is the portrait of a change. Through the contemplation of the operation and the co-ownership of this company, the film explores this space under construction, set in a setting in constant metamorphosis that serves as the framework of the daily life of dancers, construction workers, technicians and cleaners, offering a look on who we are through what we do. --